STRATEGI PENGEMBANGAN SARANA DI OBJEK WISATA CANDI MUARAJAMBI - Restianti, Risa; Yuliana, Yuliana; Ferdian, Feri (Journal of Home Economics and Tourism, 2017)
The purpose of this research is to determine facility development strategythat has indicators main tourism facility, supplementing tourism facility, andsupporting tourism facility that are viewed from internal factors form strengthsand weaknesses and external factors form opportunities and threats. This researchis a descriptive research with qualitative data. Data collection technique is done byinterview, observation, and documentation which involves informant by usingpurposive sampling technique and snow-ball sampling technique. Facilitydevelopment strategy that can be: a) Developing main tourism superstructure suchas utilizing civilian house for homestay accommodation and restaurants. b)Provide public transportation that has a special route to the tourist attraction area.c) Developing traditional food products. d) Utilizing and developing potentialland for supplementing tourist superstructure such as recreational facilities such asancient canal as a means of water tourism like game boats and fishing ponds. e)Developing handicraft product through souvenir shop in tourist area.Keywords: Strategy, development, facility